Brahms [videorecording (DVD)] : the boy II - Holmes, Katie, 1978-; Yeoman, Owain, 1978-; Ineson, Ralph, 1969- (Universal Pictures Home Entertainment, 2020)
When a young family moves to the Heelshires' residence, terror strikes when a boy from the family discovers a doll called Brahms that appears to be eerily human.